The pricing of ESG syndicated loans : an empirical analysis of spread determinants - Gonçalo, Jorge Fonseca (2022)
Sustainable financing, although recent, has shown an increasing relevance over the years in today's financial world, on its way to becoming the new standard in the corporate world. The main objective of this dissertation is to contribute to the theoretical and empirical literature on Environmental, Social, and (Corporate) Governance (ESG) syndicated loans, a topic that lacks empirical work. An analysis is made of these loans, in terms of pricing and its determinants, comparing them to conventional syndicated loans. In order to carry out these analyses, the main variables that impact the spread of these loans are empirically investigated, through comparison and regression analyses, with several robustness tests. The analyzed sample contains 17,232 loan tranches, of which 318 are classified as sustainable loans, closed between 2018 and 2022 in OECD countries. Results demonstrate that ESG syndicated loans are, on average, cheaper than conventional syndicated loans. Additionally, we draw a second conclusion, in which common factors that determine the spread of these loans have a different impact on the spread, depending on the type of loan sustainable vis-à-vis conventional.